Taming the Emotional Dog: Moral Intuition and Ethically-Oriented Leader Development - Egorov, Maxim (Journal of business ethics, 2019)
Traditional approaches describe ethical decision-making of leaders as driven by conscious deliberation and analysis. Accordingly, existing approaches of ethically-oriented leader development usually focus on the promotion of deliberative ethical decision-making, based on normative knowledge and moral reasoning. Yet, a continually growing body of research indicates that a considerable part of moral functions involved in ethical decision-making is automatic and intuitive. In this article, we discuss the implications of this moral intuition approach for the domain of ethically-oriented leader development. Specifically, we introduce a conceptual model and develop a set of theoretical propositions, suggesting that the moral intuition perspective significantly contributes to effective ethically-oriented leader development. The discussion examines theoretical implications and practical applications of the presented propositions and outlines directions for future research.